2021
DOI: 10.3390/ijms23010244
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Targeting AT1- and ETA-Receptors Link Endothelial Proliferation and Coagulation via Ets-1 Transcription Factor

Abstract: Scleroderma renal crisis (SRC) is an acute life-threatening manifestation of systemic sclerosis (SSc) caused by obliterative vasculopathy and thrombotic microangiopathy. Evidence suggests a pathogenic role of immunoglobulin G (IgG) targeting G-protein coupled receptors (GPCR). We therefore dissected SRC-associated vascular obliteration and investigated the specific effects of patient-derived IgG directed against angiotensin II type 1 (AT1R) and endothelin-1 type A receptors (ETAR) on downstream signaling event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…Under our experimental in vitro conditions, the proliferating effect of Ang II on HMEC-1s was very limited and more pronounced for AT 1 R-Abs ( Figure 1 B). Although it is possible that the previously observed differences between the two stimuli resulted from the effects of AT 2 R with native HMEC-1s (which showed no proliferation with Ang II [ 25 ]), AT 2 R anti-proliferative effects (as described in vascular smooth muscle cells (VSMCs) [ 74 ]) are here very unlikely due to AGTR1 mRNA being 100,000-fold more expressed than AGTR2 mRNA ( Supplementary Materials Figure S1 ). Furthermore, we recently showed that AT 2 R inhibitors fail to block SSc antibodies-induced endothelial cell proliferation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under our experimental in vitro conditions, the proliferating effect of Ang II on HMEC-1s was very limited and more pronounced for AT 1 R-Abs ( Figure 1 B). Although it is possible that the previously observed differences between the two stimuli resulted from the effects of AT 2 R with native HMEC-1s (which showed no proliferation with Ang II [ 25 ]), AT 2 R anti-proliferative effects (as described in vascular smooth muscle cells (VSMCs) [ 74 ]) are here very unlikely due to AGTR1 mRNA being 100,000-fold more expressed than AGTR2 mRNA ( Supplementary Materials Figure S1 ). Furthermore, we recently showed that AT 2 R inhibitors fail to block SSc antibodies-induced endothelial cell proliferation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that the previously observed differences between the two stimuli resulted from the effects of AT 2 R with native HMEC-1s (which showed no proliferation with Ang II [ 25 ]), AT 2 R anti-proliferative effects (as described in vascular smooth muscle cells (VSMCs) [ 74 ]) are here very unlikely due to AGTR1 mRNA being 100,000-fold more expressed than AGTR2 mRNA ( Supplementary Materials Figure S1 ). Furthermore, we recently showed that AT 2 R inhibitors fail to block SSc antibodies-induced endothelial cell proliferation [ 25 ]. In any case, further complementary studies are still required to determine the exact difference between Ang II- and antibodies-induced endothelial cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations